The memorial's arc: Between Berlin's Denkmal and New York City's 9/11 Memorial. (July 2016) - Young, James E
Without direct reference to the Holocaust or its contemporary "counter-monuments, " Michael Arad's design for the National 9/11 Memorial at Ground Zero is nonetheless inflected by an entire post-war generation's formal preoccupation with loss, absence, and regeneration. This is also a preoccupation they share with post-Holocaust poets, philosophers, artists, and composers: how to articulate a void without filling it in? How to formalize irreparable loss without seeming to repair it? In this article, I imagine an arc of memorial forms over the last 70 years or so and how, in fact, post-World War I and World War II memorials have evolved along a discernible path, all with visual and conceptual echoes of their predecessors. As Maya Lin's design for the Vietnam Veterans' Memorial was informed by earlier World War I and even World War II memorial vernaculars, her design also broke the mold that made Holocaust counter-memorials and other negative-form memorials possible.